2016
DOI: 10.5130/ajceb.v16i3.5178
|View full text |Cite
|
Sign up to set email alerts
|

Assessing construction innovation: theoretical and practical perspectives

Abstract: Innovation is key for productivity improvement and advancements in different sectors of the economy, including the construction sector.  The criticism of the slow pace of innovation in construction industry may be unwarranted, considering the structure of the industry and nature of the construction business.  The loosely coupled nature of firms, mostly Small and Medium Enterprises (SME’s), delivering ‘projects’ through partial engagement, together with the distinction between the project innovation and firm in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
0
22
0
1
Order By: Relevance
“…Noteworthy, the literature review identified few studies that investigated compliance in public procurement without a focus on road construction projects. Public procurement regulatory frameworks aim at promoting fairness, transparency, accountability and value for money with efficient and effective procedures benefiting all stakeholders (Agaba and Shipman, 2007;Davis et al, 2016;PPDA Authority, 2003). However, enforcing compliance with public procurement regulatory framework is challenging (PPDA Authority, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy, the literature review identified few studies that investigated compliance in public procurement without a focus on road construction projects. Public procurement regulatory frameworks aim at promoting fairness, transparency, accountability and value for money with efficient and effective procedures benefiting all stakeholders (Agaba and Shipman, 2007;Davis et al, 2016;PPDA Authority, 2003). However, enforcing compliance with public procurement regulatory framework is challenging (PPDA Authority, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Public procurement is a contractual arrangement between Government and the private sector to deliver infrastructure, goods and services (Frøystad, Heggstad and Fjeldstad, 2010). Most Government's rely on public procurement as a macroeconomic tool for economic development (Davis et al, 2016). For public procurement to achieve economic development, effective and efficient management of procurement activities is paramount (Obicci, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To meet the requirements of technological, organizational and sustainable development, construction companies or project-based organizations should seek new operational and managerial approaches to achieve a more efficient production or construction process [2,3]. The project is considered as a creative environment, where different parties with various skills and knowledge are addressing specific problems within limited time frame and resources [4]. The project-based character burdens the project management and its implementation with paradoxes and tensions, then project management processes are complex and nonlinear, which leads to an ever-changing cycle of events or requirements [5].…”
Section: Introductionmentioning
confidence: 99%
“…As such, they plead for a distinction between different types of projects while reporting on innovation in construction as the innovation potential is strongly affected by the type and size of the project. The relative lack of innovation can also be partly explained by some of the characteristics of the construction industry (Davis et al, 2016):…”
Section: Innovation In Constructionmentioning
confidence: 99%